Determining the quality of minced meat products manufactured with the use of the food additive "Laminaria+NPFe3O4" - Tsykhanovska, Iryna; Tovma, Lidiia; Lytvyn, Oleh; Alexandrov, Alexandr; Lazarieva, Tetiana; Yevlash, Viktoriia; Lushchenko, Oleh; Morozov, Ihor; Kaplun, Sergiy; Vakuliuk, Vasyl (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the quality of minced meat products (beef steaks) fortified with a nanostructured food additive of the combined composition “Laminaria + NPFe3O4”. The task addressed is to stabilize the polyphase structure and improve the consumer properties of minced meat products. It was found that introducing the additive in the amount of 0.1–0.3% improves the taste, aroma, and consistency of steaks, contributes to the formation of a more saturated and natural color, as well as increases the hardness, plasticity, elasticity, and chewiness of the products. With the introduction of the “Laminaria + NPFe3O4” food additive, the brightness of the products decreased by 1.02–1.06 times, and the b* and H* indicators increased by 1.16–1.42 and 1.08–1.43 times, respectively. The optimal concentration of the additive was determined to be 0.2%. The regularities in the influence of the nanostructured food additive of the combined composition "Laminaria + NPFe3O4", which combines components of brown algae Laminaria sp. and nanoparticles of iron oxide NPFe3O4, on the properties of beef steaks (on the transformation of pigments, the formation of textural characteristics, and sensory profile) have been established. The synergistic nature of the action of the additive components, which provides a comprehensive effect on the quality characteristics of minced meat products, has been shown, and its rational concentration at the level of 0.2% of the mass of the recipe mixture has been justified. The scope of practical application of the results includes the technology of manufacturing minced meat products. The expected effects of the implementation of the NFACC "Laminaria + NPFe3O4" are the improvement of organoleptic and textural characteristics of products and the expansion of the range of functional meat products with increased biological value